A hybrid protocol CLAG-M, a possible player for the first-line therapy of patients with mixed phenotype acute leukemia. A Polish Adult Leukemia Group experience - Karasek, Magdalena; Armatys, Anna; Skarupski, Marek; Bołkun, Łukasz; Budziszewska, Katarzyna; Drozd-Sokołowska, Joanna; Zarzycka, Ewa; Mensah-Glanowska, Patrycja; Gajewska, Małgorzata; Hałka, Janusz; Kopacz, Agnieszka; Prejzer, Witold; et al. (Frontiers in Oncology, 2024)
Introduction Mixed-phenotype acute leukemia (MPAL) is a rare disease with poor prognosis. So far, no standard approach has been established as the “know-how” of MPAL is based only on retrospective analyses performed on small groups of patients. Materials and methods In this study, a retrospective analysis of the outcomes of adult MPAL patients included in the PALG registry between 2005 and 2024 who received the CLAG-M hybrid protocol as induction or salvage therapy was performed. Results Sixteen of 98 MPAL patients received CLAG-M: eight as first-line and eight as salvage therapy. In the first line, two patients achieved partial response (PR), and six achieved complete remission (CR), of whom four successfully underwent allogeneic hematopoietic stem cell transplantation (alloHSCT). Two patients who did not undergo alloHSCT promptly relapsed. Within the whole group, the overall response rate (ORR) was 75% (n = 12/16). With the median follow-up of 13 months, six out of eight patients remain in CR, however, two of them died due to acute graft versus host disease. Out of eight patients who received CLAG-M in the second line, four patients (50%) obtained CR. AlloHSCT was conducted in seven cases, six of which were in CR. Only two patients remained in CR at the time of the last follow-up. Tolerance to treatment was good. The median times for severe neutropenia and thrombocytopenia were 22 days (range, 16–24) and 17 days (range, 12–24), respectively. Overall, grade 3-4 infections were observed in 12 cases, and all infections presented successful outcomes. Conclusions CLAG-M is an effective first-line salvage regimen for MPAL with an acceptable safety profile. Early achievement of CR with prompt alloHSCT allows for satisfactory disease control.